2022
DOI: 10.1038/s41598-022-14588-x
|View full text |Cite
|
Sign up to set email alerts
|

Odor cueing during sleep improves consolidation of a history lesson in a school setting

Abstract: Sleep is a key factor in memory consolidation. During sleep, information is reactivated, transferred, and redistributed to neocortical areas, thus favoring memory consolidation and integration. Although these reactivations occur spontaneously, they can also be induced using external cues, such as sound or odor cues, linked to the acquired information. Hence, targeted memory reactivation during sleep represents an advantageous tool for improving memory consolidation in real-life settings. In this study, our goa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…Since its initial demonstration 4 , the beneficial effect of memory cueing using odors has been shown for creativity tasks 26 , fear extinction 16 , declarative memory in a real-life setting 27,28 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since its initial demonstration 4 , the beneficial effect of memory cueing using odors has been shown for creativity tasks 26 , fear extinction 16 , declarative memory in a real-life setting 27,28 .…”
Section: Discussionmentioning
confidence: 99%
“…Since its initial demonstration 4 , the beneficial effect of memory cueing using odors has been shown for creativity tasks 26 , fear extinction 16 , declarative memory in a real-life setting 27,28 . The beneficial effect of cueing on memory has been shown to be odor-specific 15,29 , can be expressed unilaterally in the brain 14 , and is protected against interference when applied during sleep 5 , 2931 .…”
Section: Discussionmentioning
confidence: 99%
“…Our understanding about the mechanisms through which TMR impacts cognition has expanded substantially since its resurgence after the publication of Rasch et al (2007) 15 years ago, and it has recently been shown to support learning in applied settings (Gao et al, 2020;Neumann et al, 2020;Vidal et al, 2022). However, real-world memories are often complex, and it is therefore important to understand the role of sleep reactivation in supporting their retrieval.…”
Section: Future Directions and Concluding Remarksmentioning
confidence: 99%
“…We designate paradigms like the latter experiment as "simple", despite there being some variation within them (Box 1). While TMR experiments in real-world settings are scant (though see Gao et al, 2020;Neumann et al, 2020;Vidal et al, 2022), recent experiments have made inroads into how reactivation drives memory benefits and impairments in complex situations. We will review these findings and argue that an underlying theme is that consolidation trajectories are determined by the specifics of the learning experience.…”
mentioning
confidence: 99%
“…We designate paradigms like the latter experiment as “simple,” despite there being some variation within them (Box 1). While TMR experiments in real‐world settings are scant (though see Gao et al, 2020; Knötzele et al, 2023; Neumann et al, 2020; Vidal et al, 2022), recent experiments have made inroads into how reactivation drives memory benefits and impairments in complex situations. We will review these findings and argue that an underlying theme is that the specifics of the learning experience determine the consolidation trajectories of associated memories, which we refer to as the consolidation trajectory hypothesis.…”
Section: Introductionmentioning
confidence: 99%